Pengaruh Model Game Based Learning Berbantuan Educandy Terhadap Hasil Belajar IPS Siswa Kelas IV Sekolah Dasar - Audina, Mia; Ramadan , Zaka Hadikusuma (Jayapangus Press, 2025)
The problem raised in this study is related to the low learning outcomes of students, which is partly caused by the lack of enthusiasm and involvement of students in the learning process. This condition indicates the need for the application of a learning approach that is more interesting and in accordance with the characteristics of students at the elementary school level. This study aims to analyze the effect of using the game-based learning model assisted by the Educandy platform on the learning outcomes of Social Science (IPS) grade IV students at SD Negeri 138 Pekanbaru. The approach used is quantitative with pseudo experimental method with quasi experimental design with purposive sampling technique. The research sample consisted of 35 experimental group students and 33 control group students. Data collection in the study was carried out with multiple choice test questions as many as 22 items and analyzed using an independent sample test with the help of SPSS 25. Based on the results of the independent sample t-test, the average posttest value of the experimental class was 82.23 with a standard deviation of 12.317, while the control class had an average of 75.76 with a standard deviation of 14.013. This shows that the experimental class obtained higher learning outcomes compared to the control class. The significance test shows a p-value of 0.047, which is smaller than α = 0.05 (p < 0.05), so H₀ is rejected and Hₐ is accepted. This result is supported by the comparison of the tcount and ttable values, where the tcount of 2.025 is greater than the ttable of 1.668 (tcount > ttable). Thus, it can be concluded that the game-based learning model assisted by the Educandy platform has a significant effect on students' cognitive learning outcomes in social studies subjects.